(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2026)
The current study aimed to determine the degree of availability of linguistic standards in books teaching the Arabic language to speakers of other languages. It took media texts as a model and adopted a descriptive and analytical approach. The study reached the definition of linguistic standards for selecting media texts in books teaching the Arabic language to speakers of other languages, which included seven Standards and fourteen indicators, and the degree of achievement of these standards (high) degree in media texts, The current study also recommended conducting research to determine the degree of availability of cultural, social, psychological, and educational standards in books teaching Arabic to non-native speakers, and adopting linguistic standards as an entry point for building curricula for teaching Arabic to non-native speakers, and developing the entire educational system.